Person-Job Fit dan Perceived Organizational Support terhadap Komitmen Karier: Peran Mediasi Kesejahteraan Kerja: Indonesia - Alifa Indana Zulfa; Ignatius Soni Kurniawan (Universitas Hamzanwadi, 2025)
Educational quality in rural Indonesia faces challenges due to limited resources and teacher welfare concerns. This study analyzes the role of job well-being in strengthening the relationship between Person-Job Fit and Perceived Organizational Support with teachers' occupational commitment in rural areas. A quantitative survey method with saturated sampling was employed (census), involving 52 public junior high school teachers in Samigaluh, Kulon Progo. Data were collected through questionnaires and analyzed using SEM with Partial Least Squares (PLS) via SmartPLS 4.0. Results indicate that PJF has significant positive effects on both job well-being (β=0.555, p<0.001) and occupational commitment (β=0.385, p<0.001), directly and indirectly through job well-being (β=0.271, p=0.005). POS significantly influences job well-being (β=0.397, p=0.001) but does not directly affect occupational commitment (β=0.043, p=0.683). However, POS indirectly affects occupational commitment when mediated by job well-being (β=0.188, p=0.025). Job well-being serves as a crucial mediating mechanism. School management should prioritize proper teacher placement and provide tangible organizational support to enhance teacher welfare for building long-term occupational commitment